Pengaruh Tingkat Pendidikan dan Dummy Penggunaan Mesin Panen Padi (Combine Harvester) Terhadap Pendapatan Petani di Kec. Praya Barat Daya Kab. Lombok Tengah - Afifudin, Afifudin; Fitriani, Rizka (Al-Qardhu, 2025)
The thesis entitled "The Influence of Education Level and the Dummy for Using a Rice Harvesting Machine (Combine Harvester) on Farmers' Income in Praya Barat Daya District, Central Lombok Regency" is research that aims to find out whether the Educational Level and the Dummy for Using a Rice Harvesting Machine (Combine Harvester) have a significant effect. partial and simultaneous impact on Farmer Income. This research uses quantitative methods with a descriptive approach. The data collection technique was carried out by distributing questionnaires. The population in this study was 858.42 farmers in Praya Barat Daya District, and the sample used in this study was 90 respondents. The analytical method used in this research is multiple linear regression analysis. Data analysis was carried out using an analysis tool, namely SPSS. The research results show that in the t test (partial), (1) the Education Level variable (X1) has a positive and significant effect on Farmer Income (Y). (2) The Dummy Combine Harvester variable (X2) has a positive and significant effect on Farmer Income (Y). The variables Education Level (X1) and Dummy Combine Harvester (X2) simultaneously influence Farmer Income (Y) in Praya Barat Daya District, Central Lombok Regency. Keywords: Education Level, Use of Combine Harvester, Farmer Income..